Effects of cadmium on aneuploidy and hemocyte parameters in the Pacific oyster, Crassostrea gigas - Bouilly, Karine; Gagnaire, Beatrice; Bonnard, Marc; Thomas-guyon, Helene; Renault, Tristan; Miramand, Pierre; Lapegue, Sylvie (Aquatic Toxicology, 2006)
Pacific oysters, Crassostrea gigas, are commonly reared in estuaries where they are exposed to anthropogenic pollution. Much research has been made on the toxicity of cadmium to aquatic organisms because the compound recurrently contaminates their environment. Our study examined the influence of cadmium on aneuploidy level (lowered chromosome number in a percentage of somatic cells) and hemocyte parameters in C. gigas at different stages of life. Adults and juveniles were exposed to two different concentrations of cadmium. The first concentration applied was equivalent to a peak value found in Marennes-Oleron bay (Charente-Maritime, France; 50 ng L-1) and the second was 10 times higher (500 ng L-1). Exposure to 50 ng L-1 cadmium caused a significant decrease in the survival time of C gigas, but exposure to 500 ng L-1 surprisingly affected the survival time positively. Significant differences in aneuploidy level were observed between the cadmium treatments and the control in adults but not in juveniles or the offspring of the adult groups. The effects of cadmium on hemocyte parameters were analyzed by flow cytometry. Several hemocyte parameters increased significantly after 21 days of cadmium exposure and subsequently decreased. Phenoloxidase-like activity, evaluated by spectrophotometry, varied over the time of the experiment and increased after 66 days of contact with 500 ng L-1 cadmium. Taken together, cadmium at environmentally relevant concentrations seems to have only moderate effects on aneuploidy and hemocyte parameters. (c) 2006 Elsevier B.V. All rights reserved.